2015
DOI: 10.1136/openhrt-2014-000235
|View full text |Cite
|
Sign up to set email alerts
|

Treatment choices in elderly patients with ST: elevation myocardial infarction—insights from the Vital Heart Response registry

Abstract: BackgroundManagement of elderly patients with ST elevation myocardial infarction (STEMI) is challenging and they are under-represented in trials. Accordingly, we analysed reperfusion strategies and their effectiveness in patients with STEMI ≥75 years compared to <75 years within a comprehensive inclusive registry.MethodsConsecutive patients with STEMI admitted to hospital and tracked within a regional registry (2006–2011) were analysed comparing reperfusion strategy (primary percutaneous coronary intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 14 publications
5
33
0
5
Order By: Relevance
“…Although the overall reperfusion rate was as high as 91.3%, older adults were less likely to receive any reperfusion therapy, a finding that was consistent with previous research. We identified 6 primary cohort studies (including the present one) 4,9,18,21 that reported use of any reperfusion therapy at baseline and short-term mortality for Median time to death for nonsurvivors was 4 days (interquartile range (IQR) 0-8 days) for those younger than 75, 1 day (IQR 0-5 days) for those aged 75-84, and 2 days (IQR 1-6 days) for those aged 85 and older (P 5 .04). b Intracranial hemorrhage (n 5 7), cardiac tamponade (n 5 11), decrease in hemoglobin concentration of >5 g/dL (n 5 26), and death related to hemorrhage (n 5 42).…”
Section: Discussionmentioning
confidence: 99%
“…Although the overall reperfusion rate was as high as 91.3%, older adults were less likely to receive any reperfusion therapy, a finding that was consistent with previous research. We identified 6 primary cohort studies (including the present one) 4,9,18,21 that reported use of any reperfusion therapy at baseline and short-term mortality for Median time to death for nonsurvivors was 4 days (interquartile range (IQR) 0-8 days) for those younger than 75, 1 day (IQR 0-5 days) for those aged 75-84, and 2 days (IQR 1-6 days) for those aged 85 and older (P 5 .04). b Intracranial hemorrhage (n 5 7), cardiac tamponade (n 5 11), decrease in hemoglobin concentration of >5 g/dL (n 5 26), and death related to hemorrhage (n 5 42).…”
Section: Discussionmentioning
confidence: 99%
“…Stroke was defined as the development of new neurologic deficit not present on initial examination, neurologist diagnosis of stroke, or diagnosed by computed tomography imaging [16].…”
Section: Methodsmentioning
confidence: 99%
“…Как следствие всего выше изложенного, частота выполнения реперфузи-онных мероприятий у пациентов старческого возраста в реальной клинической практике значительно меньше, чем у более молодых пациентов [17,18].…”
Section: Coronary Reperfusion In Senile Patients With Acute St Elevatunclassified
“…Обна-ружено, что среди больных в возрасте 65-74 лет частота внутричерепных кровотечений составила 1,14%, а у больных ≥75 лет -1,9% [20]. Абсолютно такая же частота внутричерепных кровотечений после ТЛТ у больных ≥75 лет -1,9% -отмечена и в Канадском региональном регистре ОИМ в 2015г, т. е. на фоне уже современной противотромботической терапии [17]. Это значительно превышает частоту данного осложнения в рандомизированных исследованиях по ТЛТ.…”
Section: тромболитическая терапияunclassified
See 1 more Smart Citation